2022
DOI: 10.48550/arxiv.2207.12836
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hysteresis-Free High Mobility Graphene Encapsulated in Tungsten Disulfide

Abstract: High mobility is a crucial requirement for a large variety of electronic device applications. The state-of-the-art for high quality graphene devices is based on heterostructures made with graphene encapsulated in > 80 nm-thick flakes of hexagonal boron nitride (hBN). Unfortunately, scaling up multilayer hBN while precisely controlling the number of layers remains an elusive challenge, resulting in a rough material unable to enhance the mobility of graphene. This leads to the pursuit of alternative, scalable ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 61 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…However, defects in TMDs can induce charge disorder, diminish graphene mobility, and introduce hysteresis. Recent work has shown that devices with graphene encapsulated in superacid-treated WS 2 show minimal hysteresis, reduced charge disorder ∼10 11 cm –2 , and room-temperature mobility at or near the acoustic phonon limit. Here, we use the same methodology to establish that the WSe 2 crystals described above can serve as an ultralow-disorder substrate.…”
Section: Wse2 As a Low-disorder Substrate For Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…However, defects in TMDs can induce charge disorder, diminish graphene mobility, and introduce hysteresis. Recent work has shown that devices with graphene encapsulated in superacid-treated WS 2 show minimal hysteresis, reduced charge disorder ∼10 11 cm –2 , and room-temperature mobility at or near the acoustic phonon limit. Here, we use the same methodology to establish that the WSe 2 crystals described above can serve as an ultralow-disorder substrate.…”
Section: Wse2 As a Low-disorder Substrate For Graphenementioning
confidence: 99%
“…On this plot, the red lines show the intersection point between the constant conductivity at low density and the linear behavior at high density, which provides a good measure of the charge inhomogeneity ( n *) in the graphene . The derived value of n * = 1.4 × 10 10 cm –2 is much smaller than that achieved in the CVT device and an order of magnitude lower than that reported for superacid-passivated WS 2 . This value is well-below the concentration of defects identified as isovalent by STM (Figure above), confirming that these defects have negligible contribution to the charge inhomogeneity in the graphene.…”
Section: Wse2 As a Low-disorder Substrate For Graphenementioning
confidence: 99%